Isobolographic Antinociception of Nonsteroidal Anti-inflammatory Drugs in Rodent Formalin Orofacial Pain - Viviana Noriega; Fernando Sierralta; Nicolás Aranda; Ramón Sotomayor-Zárate; Paula Poblete; Juan Carlos Prieto; Hugo F Miranda (Mazandaran University of Medical Sciences, 2020)
Background: Diverse studies suggest that non-steroidal anti-inflammatory drugs (NSAIDs) induce antinociception through the inhibition of cyclooxygenases. Objectives: This study evaluated the effect of NSAIDs in inducing antinociception either alone or in combination in mice formalin orofacial pain. Methods: Male mice were injected intraperitoneally with dexibuprofen, dexketoprofen, diclofenac meloxicam, metamizole and piroxicam. Then from a dose-response curve the ED50 (dose that produce 50% of maximum effect) was obtained from each drug. Results: The administration of NSAIDs produced a dose-dependent antinociception in both phases of the assay with different potency. Then, combinations of the cited NSAIDs were tested and analyzed by isobolographic analysis. The results demonstrate that the nocifensive response induced when dexketoprofen (DEX), the dextrorotatory enantiomer of the S (+) configuration of ketoprofen, was combined with piroxicam, diclofenac, dexibuprofen, metamizole, and meloxicam, was synergistic, either in Phase I or Phase II of the formalin orofacial mice assay. Conclusion: The data demonstrated that the NSAIDs administered alone or in combination produce antinociception. These effects need to be explained by other mechanisms of action of NSAIDs other than the simple inhibition of COXs. The findings may be relevant for the relief of acute or chronic pain such as migraine, post‐herpetic neuralgia and tooth pain.